2014
DOI: 10.1111/jam.12449
|View full text |Cite
|
Sign up to set email alerts
|

Targeted 16S rRNA high-throughput sequencing to characterize microbial communities during composting of livestock mortalities

Abstract: Aim: A comprehensive understanding of the microbial community is necessary to ensure a significant reduction in pathogens during the composting process. Methods and Results: Two biosecure, static composting systems containing cattle mortalities were constructed at subzero temperatures. Temperature at each sampling site was measured continuously and samples were grouped as either ≤50 or ≥55°C, based on temperature exposure required for effective pathogen inactivation during composting. High-throughput 454 seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Except for D99, members from the orders Bacillales, Clostridiales, Actinomycetales, and Thermoanaerobacterales abound throughout the composting process, and most CDSs related to plant biomass degradation were classified as belonging to members of these orders. Actinomycetales are commonly found in compost, particularly in the thermophilic and mature stages11162554, and also in thermophilic microbial consortia enriched from compost3055. Indeed, in our data the relative abundance of CDSs assigned to this order involved with lignocellulosic biomass degradation is largest at D30 and D78 (34.4% and 49%, respectively).…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…Except for D99, members from the orders Bacillales, Clostridiales, Actinomycetales, and Thermoanaerobacterales abound throughout the composting process, and most CDSs related to plant biomass degradation were classified as belonging to members of these orders. Actinomycetales are commonly found in compost, particularly in the thermophilic and mature stages11162554, and also in thermophilic microbial consortia enriched from compost3055. Indeed, in our data the relative abundance of CDSs assigned to this order involved with lignocellulosic biomass degradation is largest at D30 and D78 (34.4% and 49%, respectively).…”
Section: Resultsmentioning
confidence: 49%
“…We also feature Thermopolyspora , Thermobispora, and Thermomonospora among the abundant genera within Actinomycetales. These genera comprise bacterial species that can survive the thermophilic stages of composting and are hypothesized to play an important role in biomass degradation during the composting process41213162527282930.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a study of livestock mortality compost found a predominance of Proteobacteria when temperatures were <50°C (Tkachuk et al . ), suggesting Proteobacteria are very adaptable to the type of pile and the temperature, although they prefer the later mesophilic phase of decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the past, the composting microbial community was usually studied using traditional methods such as terminal restriction fragment length polymorphism (T-RFLP), PCR denaturing gradient gel electrophoresis (DGGE), clone library, or culturing methods. As a new method for microbial community structure studies, high-throughput sequencing has increased the capacity and rate of the discovery of unknown microorganisms and given a more comprehensive picture of microbial biodiversity (Petrosino et al 2009) It has been recently used in a few studies on the composting microbial community (Tkachuk et al 2014), but those studies have focused on the start and the end of composting. Information on the evolution of the microbial community throughout the composting process is still deficient.…”
Section: Introductionmentioning
confidence: 99%